The Effect of Competency and Working Environment on Motivation and Its Impact on Employee Performance: The Case of Musi Banyuasin Regional Secretariat’s Civil Servant - Pahlawan, Reza Dwika; Fatimah, Fatimah; Moelyati, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) the influence of competence on the motivation of State Civil Apparatus employees at the Regional Secretariat of Musi Banyuasin Regency. 2) The influence of the work environment on the motivation of State Civil Apparatus employees at the Regional Secretariat of Musi Banyuasin Regency. 3) The influence of competence on the performance of State Civil Apparatus employees at the Regional Secretariat of Musi Banyuasin Regency. 4) The influence of the work environment on the performance of State Civil Apparatus employees at the Regional Secretariat of Musi Banyuasin Regency. 5) The influence of motivation on the performance of State Civil Apparatus employees at the Regional Secretariat of Musi Banyuasin Regency. This type of research is Associative. The variables used by researchers include Competence, Work Environment, Motivation, and Performance. The population of this study consisted of all ASN employees of the Regional Secretariat of Musi Banyuasin Regency, totaling 193 employees. The sample in the study comprised 120 employees, and the sampling technique used was Cluster Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM) with the LISREL Program Application. The results of this study indicate that: 1) Competence has a significant effect on the motivation of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat. 2) The work environment has no effect on the motivation of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat. 3) Competence has a significant effect on the performance of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat. 4) The work environment has a significant effect on the performance of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat. 5) Motivation has a significant effect on the performance of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat. Motivation strengthens the influence of competence and work environment on the performance of State Civil Apparatus employees at the Musi Banyuasin Regency Regional Secretariat.